2020
DOI: 10.3390/ijerph17030809
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial to Evaluate the Efficacy and Safety of the ACTLIFE Exercise Program for Women with Post-menopausal Osteoporosis: Study Protocol

Abstract: Osteoporosis (OP) is a systemic disease of the skeleton characterized by increased risk of fracture. There is a general consensus on the efficacy of physical activity in the prevention of bone loss, falls and fractures, but there is no agreement on the best setting to exercise. The aim of the study is to evaluate the efficacy of a 12-months exercise protocol for women with post-menopausal OP when administered as individual home training (IHT) versus gym group training (GGT). The study is a randomized trial wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
(56 reference statements)
0
13
0
10
Order By: Relevance
“…In addition, exercise can help to achieve beneficial and significant effects on quality of life, balance, and functional mobility also in patients with osteoporosis-related vertebral fractures (43,44). However, there is still no agreement on which type of exercise, in terms of intensity, frequency, duration, type and setting, is optimal and can affect bone metabolism in people with osteoporosis (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exercise can help to achieve beneficial and significant effects on quality of life, balance, and functional mobility also in patients with osteoporosis-related vertebral fractures (43,44). However, there is still no agreement on which type of exercise, in terms of intensity, frequency, duration, type and setting, is optimal and can affect bone metabolism in people with osteoporosis (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Details on study methods have been published previously [ 21 ]. Briefly, postmenopausal women with OP were recruited by the Centro Osteoporosi e Malattie Metaboliche dello Scheletro of Rizzoli Orthopaedic Institute of Bologna, Italy, and had no significant comorbidities affecting motor or cognitive functions.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the trainer contacted the IHT participants at pre-established time intervals to encourage them to exercise regularly and to obtain information on their health status. Every 6–8 weeks, a face-to-face appointment was scheduled to review and upgrade the exercise program [ 21 ], based on the progression principle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A healthy and active lifestyle is vital for the proper maintenance of all body tissues, including bone. Several studies have highlighted the importance of physical exercise to improve the quality of life of patients with osteoporosis [92][93][94]. Recently, Filipović, T. et al 2020 [95], has demonstrated that exercising is able to modulate the enzymatic activity of serum matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase 1 (TIMP-1) in postmenopausal osteoporotic patients.…”
Section: Osteoporosis Treatmentsmentioning
confidence: 99%